Ta’tsîru Istikhdâmi Washîlah Wordwall Litarqiyati Natâiji al-Lughah al-Arabiyah ladâ at-Thullâbi bi al-Madrasah al-Ibtidâiyyah al-Islâmiyyah al-Ahliyah Insan Cendekia Bangkinang - Amelia, Cindy; Nurhasnah, Nurhasnah; Arsya, Fajriani; Yusra, Oktarina (Al-Manar, 2025)
The purpose of this study to reveal the Effect of the Use of "Wordwall" Media to Improve the Learning Outcomes of Arabic Language for Students at SDIT Insan Cendikia Bakinang. The research approach used is a quantitative approach with the type of experimental research. The design used an experimental design based on field research. The collection tools are observation data, interviews, documents. The data analysis method used by the researcher is quantitative data analysis withSPSS. The results of the study can be concluded: 1) The results of the analysis show that the learning outcomes of the students are increasing, it can be seen that the results of the post test there are many students who obtained higher scores than from the control class, the post test score of the experimental class is83.25 inthe control class students obtained a score of  75.25. 2) there is an influence from the "Wordwall" media to improve the learning outcomes of third grade students at SDIT Insan Cendikia Bakinang. With a significance value of 00.1 less than 00.5, with a demic .